Automatic recorders monitor wolves at rendezvous sites: do wolves adjust howling to live near humans? - Palacios, Vicente; Martí-Domken, Bárbara; Barber-Meyer, Shannon M.; Habib, Bilal; López-Bao, José V.; Smith, Douglas W.; Stahler, Daniel R.; Sazatornil, Victor; García, Emilio J.; Mech, L. David (Biodiversity and Conservation, 2023)
We used automatic sound recorders to study spontaneous vocalizations of wild wolves during the pup-rearing season around rendezvous sites from 24 wolf packs in six study areas across North America, Asia, and Europe. Between 2018 and 2021, for a total of 1225 pack-days, we recorded 605 spontaneous wolf chorus howls and 224 solo-howl series. Howling occurrence varied across areas, from 12.50 to 94.12% days with howling. Daily howling ranged from 0.00 to 3.47 solo howls/day and 0.13 to 5.29 chorus howls/day. Generally, spontaneous chorus howls peaked between sunset and sunrise. Howling rate depended on area, pack size, and density of people living nearby, being greater where fewer people lived. High rates in Yellowstone National Park, (800,000+ visitors during the study) could reflect accommodation to human activities such as wolf watching. One to six automatic recorders per site within 1000 m of rendezvous sites needed 4–15 days to detect the pack (average 9.5) and 5–21 days (average 11.3) to detect pups, both with a probability of 95%. Our results may guide wolf-monitoring programs using automatic sound recorders, a promising method offering advantages over howling surveys, especially in human-dominated landscapes. Funding was provided by the National Geographic Society (Grant Number NGS-59729R-19) and the U. S. National Park Service. JVLB was supported by the Spanish Ministry of Economy, Industry and Competitiveness (RYC-2015-18932, CGL2017-87528-R AEI/FEDER EU), by the Regional Government of Asturias, and by a GRUPIN research grant from the Regional Government of Asturias (IDI/2021/000075). Peer reviewed